2016
DOI: 10.1038/bcj.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib and the cardiorenal system in myeloma: an endothelial effect?

Abstract: Carfilzomib (Cfz) has been associated with an ~5% incidence of unexplained and unpredictable cardiovascular toxicity in clinical trials. We therefore implemented a detailed, prospective, clinical cardiac and renal evaluation of 62 Cfz-treated myeloma patients, including serial blood pressure (BP), creatinine, troponin, NT-proBNP and pre- and post-treatment echocardiograms, including ejection fraction (EF), average global longitudinal strain and compliance. Pre-treatment elevations in NT-proBNP and BP, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 18 publications
0
56
0
4
Order By: Relevance
“…Careful clinical volume status assessment may be a useful measure to proactively manage patients at risk for developing heart failure. Increasing evidence suggests a possible effect of proteasome inhibition on vascular endothelium, [34][35][36][37] rather than cardiac myocytes. Therefore, vascular impact biomarkers should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Careful clinical volume status assessment may be a useful measure to proactively manage patients at risk for developing heart failure. Increasing evidence suggests a possible effect of proteasome inhibition on vascular endothelium, [34][35][36][37] rather than cardiac myocytes. Therefore, vascular impact biomarkers should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology remains unknown, but endothelial effects 41 and inhibition of proteasome-dependent sarcomeric protein turnover in cardiomyocytes 42 have been discussed as contributing factors. Cardiac failure is thought to be a class effect of PIs because it has also occasionally been reported with bortezomib 43 and ixazomib.…”
Section: Comments About Patient 2 Cardiac Failurementioning
confidence: 99%
“…Hypertension and any other cardiovascular risk factors should be adequately controlled prior to starting carfilzomib. During treatment, regular clinical surveillance with blood pressure control is recommended; serial monitoring of cardiac function by echocardiogram 47 or cardiac biomarkers such as N-terminal prohormone of brain natriuretic peptide 41 are considered of limited value in mitigating the risk for carfilzomib-induced cardiac failure. Whenever cardiac failure is suspected, carfilzomib treatment should be discontinued and a detailed cardiopulmonary evaluation performed.…”
Section: Comments About Patient 2 Cardiac Failurementioning
confidence: 99%
“…The exact mechanism has not yet been clarified, but an effect of carfilzomib on endothelial cells and a common acute rise in NT-proBNP has been reported. 83 A decline in ejection fraction in few patients was shown. 83,84 In the ENDEAVOR study, events of heart failure and pulmonary hypertension were more frequently reported in Kd versus Vd patients and similar findings were also reported in the CLARION study comparing KMP with VMP.…”
Section: Cardiac and Vascular Toxicitiesmentioning
confidence: 97%
“…83 A decline in ejection fraction in few patients was shown. 83,84 In the ENDEAVOR study, events of heart failure and pulmonary hypertension were more frequently reported in Kd versus Vd patients and similar findings were also reported in the CLARION study comparing KMP with VMP. 85 Reported reductions in left ventricular ejection fraction were mostly reversible.…”
Section: Cardiac and Vascular Toxicitiesmentioning
confidence: 97%